HUBUNGAN PELAYANAN IMUNISASI DI PUSKESMAS DENGAN CAKUPAN IMUNISASI DASAR LENGKAP PADA ANAK DI PROVINSI SUMATERA UTARA DAN PROVINSI KEPULAUAN RIAU - Yahya, Yahya; Salim, Milana; Oktarina, Reni (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2014)
Immunization services directed towards preventive efforts against the occurrence of a disease or health problem The implementation of immunization services cannot be separated from the role of health workers and their competence in accordance with task and functions. According to the result of Basic Health Research 2010, Kepulauan Riau Province occupies the first place in Sumatera in the achievements of complete immunization coverage (74,4%) and has the lowest amount for children who have not been immunized (5,1%). North Sumatera Province has the lowest number of complete immunization coverage than other provinces in Sumatera (33,3%) with the number of children who have not been immunized reached 23,6%. This analysis was aim to know factors of immunization service in Puskesmas that affect the coverage of children (12-23 month) who have complete basic immunization and timely. Data selected from the province who have highest complete immunization coverage (Kepulauan Riau Province) and lowest (North Sumatera Province) in Sumatera region. The result showed that there was no relationship between the frequency of immunization services inside the building (p value 0,481), the availability of immunization service outside the building (p value 0,631), the number of immunization officers (p value 0,282), the number of immunization officers who attend immunization technical training (p value 0,965), the number of immunization officers who attend KIPI training against complete immunization coverage (p value 0,955).